1997
DOI: 10.1177/088307389701200807
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography in Children With Neurofibromatosis-1

Abstract: Neurofibromatosis-1 is an autosomal dominant genetic disorder commonly associated with neuropsychological complications. Focal areas of high signal intensity on magnetic resonance imaging (MRI) scans occur commonly but have shown inconsistent correlation with neuropsychological problems. Positron emission tomography (PET) scans utilizing [18F]fluoro-2-deoxy-D-glucose and MRI studies were performed on 10 children with neurofibromatosis-1 and multiple focal areas of high signal intensity to evaluate the regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
25
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 19 publications
6
25
0
Order By: Relevance
“…Prior FDG-PET studies in NF-1 [35][36][37] have shown abnormal cerebral metabolism similar in distribution to the perfusion pattern noted in this study, for example, global hypometabolism with a more marked hypometabolism in the posterior brain regions. For example, in 4 adolescents with NF-1 (9 -20 years of age), global hypometabolism with a more marked reduction of FDG activity in the thalamus and the occipital lobes was noted with intact metabolism in the striatum.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Prior FDG-PET studies in NF-1 [35][36][37] have shown abnormal cerebral metabolism similar in distribution to the perfusion pattern noted in this study, for example, global hypometabolism with a more marked hypometabolism in the posterior brain regions. For example, in 4 adolescents with NF-1 (9 -20 years of age), global hypometabolism with a more marked reduction of FDG activity in the thalamus and the occipital lobes was noted with intact metabolism in the striatum.…”
supporting
confidence: 79%
“…17,36,37 Marked reduction in CBF in the thalamus and variable alterations in cortical perfusion in our study also implicate these brain regions, potentially reflecting underlying dysgenesis or a dysfunction in their relationship, or underlying arteriopathy as a source of cognitive deficits, not unlike the adult model for vascular dementia. 38 In the present study, we used ASL perfusion to measure CBF because it directly quantifies CBF by use of in-flowing arterial protons as an endogenous tracer 39,40 and has additional advantages in children because of the high labeling efficiency and signalto-noise ratio.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…More than 10 years later, PET has not become routinely used in neuropediatrics and the literature on this area remains relatively scarce [14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25]. However, PET is still considered an important tool to elucidate the complexity of the developing brain or to evaluate neurodegenerative disorders and cognitive abnormalities [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] To test whether the lack of an effect in the thalamus of NF1+/ − mice in the in vivo SPECT experiments was because of targeting perfusion rather than glucose metabolism (or a true interspecies difference), we performed postmortem well-counter measurements of FDG uptake in the thalamus of NF1+/ − and WT mice. Postmortem wellcounter measurements avoid partial volume effects inevitable in in vivo PET imaging.…”
Section: Ex Vivo Measurement Of Thalamic F-18-fluorodeoxyglucose Uptakementioning
confidence: 99%